The INFLUENCE OF PARENTS' VERBAL VIOLENCE ON EARLY CHILDREN'S LANGUAGE DEVELOPMENT IN PAUD SAFINATURRAHMAH TELUK KABUNG, GAUNG DISTRICT, INDRAGIRI HILIR DISTRICT: Verbal Violence, Language Development - Rahmah Rahmah; Susi Herlinda; Sumanti Sumanti; Asri Nelli Putri (E-JURNAL AKSIOMA AL-ASAS, 2026)
Parental verbal violence is violence perpetrated by parents against children in the form of violence against feelings, saying harsh words without physical contact, words such as threatening, insulting, comparing, and so on. Verbal violence can affect a child's development, especially the child's language development. The formulation of the problem in this research is what is the influence of parental verbal violence on early language development in Safinaturrahmah PAUD. The aim of the research is to determine the influence of parental verbal violence on early language development in Safinaturrahmah PAUD. The form of research carried out is quantitative with an ex post facto method. This research uses a saturated sample or the sample is taken as a whole. The population in this research is 30 respondents. And the data collection technique used in this research is a test questionnaire. Then for the data analysis technique the author uses the Chi-Square analysis technique and the contingency coefficient test to measure how big the influence.Based on hypothesis testing carried out with SPSS, the R Square value is 0.25.1 or equal to 25.1%. This figure means that verbal violence (X) influences the child's language development variable (Y) by 25.1%. The Chi-Square table results are 30.612 and the Sig value. = 0.003. This means that the Chi-Square value > Chi-Square table (51.556 > 30.612), then Ha is accepted and Ho is rejected. Then the Contingency Coefficient test result of 0.892 is between the values of 0.80-1.000 and is included in the very strong category. So these results show that verbal violence has an influence on Early Language Development in Safinaturrahmah PAUD.